The Acheulean site of la Noira (Centre region, France): Characterization of materials and alterations, choice of lacustrine millstone and evidence of anthropogenic behaviour. (8th August 2016) - Despriee, Jackie; Courcimault, Gilles; Moncel, Marie-Hélène; Voinchet, Pierre; Tissoux, Hélène; Puaud, Simon; Gallet, Xavier; Bahain, Jean-Jacques; Moreno, Davinia; Falgueres, Christophe
Abstract: The Acheulean site of la Noira was fossilized beneath the Fougères fluviatile formation dated by the ESR method at 655 ± 55 ka. Coarse deposits were left at the base after the end of the Cher incision and served as raw material deposits for hominins. The occupation level has yielded bifaces, cores and a flake assemblage in lacustrine millstone. The systematic recording of about 6 500 lithic objects brought to light the reasons underlying the presence of the diverse materials, and elucidated hominin choice of lacustrine millstone for knapping flakes and shaping bifacial pieces. The systematic study of all the materials enabled us to advance hypotheses concerning some of the behaviour identified at the site: sorting of raw materials affected by frost, cursory peripheral knapping of slabs of up to a metre long with hammers weighing several kilogrammes, breaking up of large slabs over 10 cm long and displacement of the fragments. This analysis assesses hominin behaviour and the management and exploitation of raw material deposits at 700 ka.